PELATIHAN CARA PENULISAN BUKU DAN ARTIKEL ILMIAH BAGI GURU SDN 31 TEGINENENG KABUPATEN PESAWARAN - Henry Susanto; Rinaldo Adi Pratama; Yusuf Perdana; Valensy Rachmedita (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
A professional teacher must have four competencies, namely pedagogical competence, personality competence, social competence and professional competence. Professional competence, namely the ability of teachers to master knowledge in the field of science, technology or cultural arts that they teach. Mastery of these abilities should be expressed by the teacher, one of which is by making or writing scientific articles. There are many things that educators need to pay attention to in writing scientific books and articles in order to achieve proper scientific books and articles and become references for other educators. However, it cannot be denied that there are still many school teachers who do not know how to make textbooks and scientific articles. This unfavorable reality occurs not only as an error as educators who do not know or understand but because of limited knowledge, limited resources that make it difficult for them to make textbooks or scientific articles. In addition, the lack of training provided at whole level on how to make scientific books and articles makes it more difficult for educators to gain knowledge about these matters. Therefore, the team conducts training for elementary school teachers on how to write scientific books and articles whose material includes explanations of textbooks and scientific articles, ways of making, the structure of each compilation, the language used, how to find references and how to publish an article. scientific papers and examples of journals that can serve as a forum for publication of scientific articles. After community service was carried out regarding training on how to write books and scientific articles, there was an increase in the teacher's understanding of textbooks and articles, namely the average before service was 47.14% after training there was a significant increase in an average of 63.57%.